Tripanossomose bovina em Minas Gerais, 2011: soroprevalência e fatores de risco - Rodrigo Melo Meneses (2016)
Bovine trypanosomosis is responsible for great economic losses in Africa and Latin America. In the Americas, Trypanosoma vivax is the mainly cause for the disease in cattle, being mechanically transmitted by blood-sucking insects and fomites. The agents of the disease were brought to South America for the first time, from Africa, through imported animals, caracterizing its origin in the Americas. The first report was emited in the north of Brazil, with subsequent spread to the Pantanal and, in the last decade, outbreaks were reported in several regions of the country, including Minas Gerais. The research objective was to determine the serological prevalence of bovine trypanosomosis and identify risk factors associated with the disease in Minas Gerais state. In 2011, a cross sectional study was performed in Minas Gerais, in which the state was divided into seven regions according to agricultural production characteristics: 1. Northwest, North and Northeast; 2. Eastern; 3. Central; 4. Forest Zone; 5. South and Southwest; 6. Alto Paranaíba; 7. Triângulo Mineiro. Among all regions, 2185 properties were sampled randomly, of which serum samples were collected and subjected to indirect immunofluorescence assay for the detection of anti-T. vivax. The prevalence for bovine trypanosomosis on properties in Minas Gerais state was 2.38% (95% CI: 1.68 to 3.08%). Among strata the prevalence ranged from 0.69% in the eastern region (stratum 2) to 3.7% in the South and Southwest (stratum 5), but there was no significant difference. Risk factor analysis indicated that herds in which the owners claimed to perform brucellosis test and to buy animals from cattle traders, had greater chance of occurrence of the disease, with an odds ratio of 2.75 (95% CI: 1.37 to 5.51) and 3.36 (95% CI: 1.31 to 8.59), respectively. There was no presence of agglomerated between farms with animal serum reagents. This study is the first to reveal the prevalence of bovine trypanosomosis in Minas Gerais state. Results showed that the prevalence was low, however the disease was already homogeneously distributed throughout the state. Additionally, perform brucellosis test exerts indirect influence on the occurrence of the disease, while buying animals from livestock dealers have a direct impact on the occurrence of bovine trypanosomosis in Minas Gerais, requiring health education for owners and use of biosecurity measures in the properties.